ASPECTS OF STUDYING THE PHYSICO-CHEMICAL PROPERTIES OF LOCAL AMARANTH OILS OF HIGH-CONTAINING SQUALENE - Akramova Rano Ramizitdinovna; Rasulova Umida Nematjon qizi; Yuldasheva Nigora Karimovna; Ashurmatova Gulchexra Isamiddinovna (Journals Park Publishing, 2022)
In the course of the work, it is supposed to find out the amaranth of local origin. the study of the physico-chemical and pharmacological properties of amaranth oil, as well as consideration of the prospects for the introduction of the product in the field of functional nutrition and cosmetology.
Keywords: amaranth oil; neutral lipids; fatty acids